(untitled) (BIRDEM Medical Journal, 2016)
Objective: The study was aimed to describe the patterns of single anti-diabetic agents used by type 2 diabetic patients and their glycemic status during hospital admission. Study design and methods: This cross-sectional study was carried out in BIRDEM among hospitalized type 2 adult diabetic patients of different ages and both sexes. Data were collected during admission that included detailed history, medical records review, clinical examination and laboratory investigations. Results: Subjects (n=253; 174 female, 79 male) had age (years) as mean ± SD: 55.28 ±13.45 (15- 90 years), BMI (kg/m2) as mean ±SD: 24.67±4.97 and HbA1c (%) as mean ±SD: 10.56±2.98. Use of pre-mixed insulin 90 (35.57%) and split-mixed insulin 70 (27.66%) were more common than other drugs. Glycaemic control was poor in all age groups as evidenced by raised HbA1c, significantly higher in patients <40 years age group. Blood glucose profiles were also high among the all age groups. HbA1c and blood glucose profiles both were high irrespective of type of anti-diabetic agents used during admission. It was also found that patients with increasing age groups were using insulin more frequently. BMI categorization had no significance within treatment groups. (p=0.453). Conclusion: There was no significant difference in blood glucose control among the different single anti-diabetic drug users, that might be due to treatment of diabetes includes medical nutrition therapy with judicious and individualized dietary plan, lifestyle modification, effective exercise plan, and individualized target oriented use of anti-diabetic agents. Along with proper selection of anti-diabetic agents, patients self-management education and disease-specific awareness is essential to achieve good glycemic control. Birdem Med J 2015; 5(2): 92-97